EFEKTIFITAS BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DALAM PERLINDUNGAN HUKUM TENAGA KERJA DI KABUPATEN BOGOR - Hazarul, Harry (JURNAL ILMIAH LIVING LAW, 2016)
In Indonesia, everyone is entitled to social security to be able to meet the basic needs of a decent life and enhance the dignity of Indonesian society towards the realization of a prosperous, equitable, and prosperous. In order to create a foundation to improve the welfare and protection of labor, laws regulating the conduct of the Badan Penyelenggara Jaminan Sosial (BPJS) as the embodiment of social insurance. Results of this research are: 1) Implementation of social security health workers in Bogor is needed by laborers ; 2) The legal protection of social security health workers in Bogor, has not been done as it should be, there are still many laborers who have not registered for the social security health, due to lack of awareness and reluctance of employers in implementing social security programs of health ; 3) Effectiveness of Social Security Health in the protection of labor law in Bogor through BPJS Kesehatan as a social security already meet the elements of social security protection, but in practice there are still obstacles either to do with regulations or rules there is the realization and many complaints against the services and benefits held BPJS Kesehatan.